Pengaruh Pemberian Reward and Punishment terhadap Kedisiplinan Belajar Siswa Kelas V SSD HKBP Batu IV T.P 2022/2023 - Rosvita Monika Damanik; Nancy Angelia Purba; Partohap Saut Raja Sihombing (Departement of Mathematics Education, 2023)
The purpose of this study was to determine the effect of reward and punishment on the learning discipline of fifth grade students at SDS HKBP Batu IV T.P 2022/2023. This type of research is quantitative research with non-experimental methods. The population in this study were 27 students of class V SD. The sample used was 27 students with total sampling technique. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that (1) There is a positive and significant influence between giving rewards to student learning discipline with tcount (3.412 > 1.710) and a sig value of 0.002 <0.05. (2) There is a positive and significant influence between Punishment on Student Learning Discipline with tcount (2.546 > 1.710) and a sig value of 0.018. (3) The contribution of the two variables is 61.4% while 39.6% is influenced by other variables not studied in this study. (4) The multiple linear equation in this study is Y = 62,725 + 0.256 X1 + 0.058 X2. Based on the statement above, it can be concluded that the provision of reward and punishment affects the learning discipline of Class V students at SDS HKBP Batu IV T.P 2022/2023.